Pengembangan Jaringan Distribusi Air Minum Wilayah Pelayanan Instalasi Pengolahan Air Minum (IPA) Tegal Gede Kabupaten Jember - Atika Nugraheni Ainun Nisa (Fakultas Teknik, 2025)
Perumdam Tirta Pandalungan in Jember Regency plans to expand the IPA Tegal Gede service area to include Antirogo Village and Baratan Village. To Address the community’s waterneeds, Perumdam tirta Pandalungan will upgrade existing facilities and add a new water treatment plan in Tegal Gede service area. This study aims to determine the water requirement of the community in IPA Tegal Gede service area until 2043 and identify the most efficient distribution network model for development. Water needs are calculated based on population projections until 2043, wich are conducted using three methods: Linear, Exponential, and Logistic trend methods. The development network model is evaluated across four scenarios, simulated using Epanet 2.2 to illustrate the hydraulic performance of the piping network with the corresponding cost requirement, calculated based on AHSP Kabupaten Jember 2024. According to the population projections, teh total drinking water needs for the community in IPA Tgeal Gede service area is estimated to be 104,47 liters/second by 2043. In terms of technical aspects, the best scenario to implement is scenario 2, which has a pressure range of 21.35–65.67 m and a speed of 0.34–1.10 m/s during peak usage hours, and a pressure range of 44.55–68.54 m and a speed of 0.34–0.58 m/s during minimum usage hours. In terms of cost, the scenario that requires the least cost is scenario 1, which is Rp717,668,326.00.
Entry oleh Arif 2026 April 02
Keywords: Drinking water; Epanet; Network Development